Impact of individual characteristics and telecentre success in Malaysia - Bashir, Muhammad Sani; Abu Samah, Bahaman; Emby, Zahid; Mohamed Shaffril, Hayrol Azril (American-Eurasian Network for Scientific Information, 2011)
Information and Communication Technology is an important impetus for rural development nowadays. Parallel with this, the Malaysian government has introduced rural telecenter known as Pusat Internet Desa which in English called Rural Internet Center for the purpose of developing the rural community. To ensure its success and its objectives fulfilled, Rural Internet Center has offered a lot of benefits for its users such as developing computer and internet skills, increase their knowledge and widening their networking, but do the rural community utilize the services provided in the telecenter, if yes, are the individual Characteristics such as age, education and computer skills do influence the success of this telecenter. This is a quantitative study where through a stratified random sampling a total of 138 respondents were selected and these selected respondents were the users of the telecenter. Results gained have proved that computer skill have a positive and significant relationship with telecenter success while age and education were detected to have no any significant relationship with telecenter success. It is recommended that number of computer training can be doubled while house to house training conducted by related agencies can be conducted.